Augmented Manufacturing - López Rodríguez, Álvaro (REIA - Revista Europea de Investigación en Arquitectura, 2023)
The evolution of digital technologies and their rapid adoption by our society is shifting traditional paradigms. The normally conservative industry of architecture is now leading the integration of new techniques in multiple ways. Technologies like 3D printing, robotic automation, platform-based apps and Mixed Realities are changing architecture workflows. Using these interfaces, designers and builders are leaving the Post-Industrial Age to enter the Augmented Age. Looking towards the near future, the use of Mixed Reality technology will change the traditional role of the workforce, enhancing and extending their skills. Future workers will have access to real-time skills and guidance through augmentation, facilitating and preserving traditional craftsmanship and integrating them simultaneously with computational architecture. This research explores how the application of augmented reality can challenge the concept of the traditional artisan and propose a new approach to the access of skills and labour in manufacturing methodologies for the architectural environment. The analysis will review the impact of mixed realities by studying three study cases themed into two different topics, craftsmanship and digital platforms.